Effects of temperature in novel crimp-free based composite materials for aerospace applications: An experimental assessment - Marcello A. Lepore (Elsevier, 2021)
This work shows the effects produced on mechanical behaviour by cold and elevated temperatures in a novel Non-crimped Fabric (NCF) composite for aerospace use. A mechanical characterization of the new composite was performed through several experimental tests. Composite plaques with different ply orientation, number of plies and thicknesses were produced through the Resin Transfer Moulding (RTM) process. Coupons required for mechanical characterisation of the composite were obtained from each of these plates using a well-designed plate cutting plane. The experimental tests were performed in a certified laboratory with electromechanical machines and according to ASTM standards. To characterize the mechanical behaviour of the composite material at elevated and cold temperatures, experimental tests were carried out in a controlled temperature environment and the results were compared with those obtained from previous tests at room temperature. This comparison was necessary to understand if the new composite can be used as a structural component for aerospace. Finally, an analysis of the variation coefficient was carried out, on the basis of the statistical average of the parameters calculated with the experimental tests, to evaluate the reproducibility of the tests in different laboratories.